2016
DOI: 10.1109/tkde.2016.2553667
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Political Leaning from Tweets, Retweets, and Retweeters

Abstract: The widespread use of online social networks (OSNs) to disseminate information and exchange opinions, by the general public, news media and political actors alike, has enabled new avenues of research in computational political science. In this paper, we study the problem of quantifying and inferring the political leaning of Twitter users. We formulate political leaning inference as a convex optimization problem that incorporates two ideas: (a) users are consistent in their actions of tweeting and retweeting ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
114
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(120 citation statements)
references
References 35 publications
2
114
0
4
Order By: Relevance
“…Zafar et al (2016), have quantified the impartiality of social media posts by measuring how easy it is to guess the political leaning of its author. Bond and Messing (2015) inferred the political leanings of Facebook users by observing the endorsements of Facebook Pages of known politicians, while Wong et al (2016) measure the endorsements in terms of retweeting behavior of users to infer their political leanings. Cohen and Ruths (2013) used supervised methods to classify users into different groups of political activities and showed that it is hard to infer the political leaning of "normal" users.…”
Section: Measuring Political Bias On Social Media and The Webmentioning
confidence: 99%
“…Zafar et al (2016), have quantified the impartiality of social media posts by measuring how easy it is to guess the political leaning of its author. Bond and Messing (2015) inferred the political leanings of Facebook users by observing the endorsements of Facebook Pages of known politicians, while Wong et al (2016) measure the endorsements in terms of retweeting behavior of users to infer their political leanings. Cohen and Ruths (2013) used supervised methods to classify users into different groups of political activities and showed that it is hard to infer the political leaning of "normal" users.…”
Section: Measuring Political Bias On Social Media and The Webmentioning
confidence: 99%
“…Many build learning models that are applicable across a variety of different user attributes (Chen et al, 2015a;Volkova et al, 2015;Beretta et al, 2015). Among the attributes, political preferences is a frequent area of research, again relying on features from user tweets, and making use of graph-based algorithms over their friends' attributes (Golbeck and Hansen, 2011;Conover et al, 2011;Wong et al, 2013;Cohen and Ruths, 2013;. Pla et al (2014) even uses sentiment analysis.…”
Section: Previous Workmentioning
confidence: 99%
“…Characterizing social media users based on their political affiliation is an ongoing challenge in Natural Language Processing and Computational Social Science (Conover et al, 2011;Cohen and Ruths, 2013;Sylwester and Purver, 2015;Wong et al, 2016). In addition, linguistic reflections of political identity are of interest to sociolinguists (Hall-Lew et al, 2010;Labov, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Sylwester and Purver, who were interested in characterizing psychological differences between Democrats and Republicans, focused on word frequency, friend-follower ratio and Linguistic Inquiry and Word Count (Pennebaker et al, 2001)-although they also excluded punctuation from their data. Another study by Wong et al used no linguistic features at all, relying instead on social network relations with users whose political affiliation was known (Wong et al, 2016). Much of the sociolinguistic work, on the other hand, has focused on sub-lexical features that encode political identity.…”
Section: Introductionmentioning
confidence: 99%